Seismic behavior of Chuan-dou timber frames with different infilled walls. (11th April 2022) - Liang, Wei; Lan, Jie; Zou, Zuyin; Zhu, Zhanyuan; Zhai, Shuainan; Mo, You; Li, Xiaomei; Meng, Sihui; Cai, Yu
Highlights: An unsimplified test model based on an actual Chuan-dou wooden structure house was adopted. Behavior of typical wall-filled Chuan-dou timber frames subjected to in-plane cyclic loading was studied. The influence of the slip of the column foot on the seismic behavior was analyzed. Abstract: The Chuan-dou timber frame is a structural system that is most suitable for natural factors such as local topography and climatic environment, and used by the people in southwestern China after thousands of years of production and life. In this study, a standard frame of a typical two-story Chuan-dou timber structure in southwestern China was used as a prototype, and three Chuan-dou timber frame models with a scale of 1:2 were designed and produced. The models were one Chuan-dou timber frame without infilled walls (PWF), one Chuan-dou timber frame with infilled wooden panels (WWF), and one Chuan-dou timber frame with infilled brick walls at the bottom and infilled plasterboard at other parts (BWF). Through a quasi-static cyclic test, the force–deformation characteristics, failure modes, stiffness degradation behavior, and energy dissipation capacity were investigated. The results showed that PWF had good deformation property, but its stiffness and ultimate load carrying capacity were low. Compared with PWF, the lateral strength and stiffness of WWF and BWF were effectively improved, but the compatible deformation capability of the brick wall and the frame was poor due to the weak connection between them. In addition, increasing the connection capacity between the column foot and ground to restrict the sliding of the column foot could be a proper way to improve the deformation and energy dissipation capacity of timber frame.